2021
DOI: 10.5194/acp-21-8709-2021
|View full text |Cite
|
Sign up to set email alerts
|

Insights into seasonal variation of wet deposition over southeast Asia via precipitation adjustment from the findings of MICS-Asia III

Abstract: Abstract. Asia has attracted research attention because it has the highest anthropogenic emissions in the world, and the Model Inter-Comparison Study for Asia (MICS-Asia) phase III was carried out to foster our understanding of the status of air quality over Asia. This study analyzed wet deposition in southeast Asian countries (Myanmar, Thailand, Lao People's Democratic Republic (PDR), Cambodia, Vietnam, the Philippines, Malaysia, and Indonesia) with the aim of providing insights into the seasonal variation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This is consistent with previous studies. For example, Itahashi et al (2021) have investigated the seasonal variation of wet deposition over Southeast Asia based on observations and model simulations. They showed that wet depositions of aerosol components were much smaller in winter and spring than those in summer and autumn in MSEA areas such as Thailand, Vietnam, and Cambodia.…”
Section: Influence Of Bb Emissions On Aerosol Depositions In the Nscs...mentioning
confidence: 99%
“…This is consistent with previous studies. For example, Itahashi et al (2021) have investigated the seasonal variation of wet deposition over Southeast Asia based on observations and model simulations. They showed that wet depositions of aerosol components were much smaller in winter and spring than those in summer and autumn in MSEA areas such as Thailand, Vietnam, and Cambodia.…”
Section: Influence Of Bb Emissions On Aerosol Depositions In the Nscs...mentioning
confidence: 99%
“…BS coefficient for aerosol (specially referred to as Λ hereafter), the key in characterizing aerosol BS process, is parametrized diversely in CTMs, reflecting variations in the limited observations (Chin et al., 2000; Lu & Fung, 2018). This inevitably causes differences in simulated aerosol burden (Croft et al., 2009, 2010; Lu & Fung, 2018; Textor et al., 2006) and wet deposition (Ge et al., 2020; Itahashi et al., 2020, 2021; Z. Wang et al., 2008), and then limits the accurate assessments of their climate (Choi et al., 2020; J. Xu et al., 2019) and ecological effects (Vivanco et al., 2018). Specifically, the Λ for fine particle (PM 2.5 ) in CTMs (10 −6 –10 −5 s −1 ) is mostly 1–2 orders of magnitudes lower than measurements (10 −5 –10 −4 s −1 ) (Ge et al., 2021; D. Xu et al., 2019), which probably leads to an underestimation of BS.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the Λ for fine particle (PM 2.5 ) in CTMs (10 −6 –10 −5 s −1 ) is mostly 1–2 orders of magnitudes lower than measurements (10 −5 –10 −4 s −1 ) (Ge et al., 2021; D. Xu et al., 2019), which probably leads to an underestimation of BS. This underestimation is responsible for underpredicting wet deposition for SO42 ${\text{SO}}_{4}^{2\mbox{--}}$, NO3 ${\text{NO}}_{3}^{\mbox{--}}$, and NH4+ ${\text{NH}}_{4}^{+}$ (SNA) in East Asia (medians for corresponding species: 32%–64%, 9%–55%, and 10%–16%) (Ge et al., 2020; Itahashi et al., 2020, 2021; Luo et al., 2020), Europe (12%–58%, 20%–31%, and 19%–33%) (Dentener et al., 2006; Luo et al., 2020; Simpson et al., 2006; Theobald et al., 2019; Vet et al., 2014; Vivanco et al., 2018) and the USA (21%–35%, 53%–68%, and 10%–48%) (Luo et al., 2020; Nopmongcol et al., 2019; Vet et al., 2014; Y. Zhang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations